Early‐mid adulthood measures of HDL, triglycerides and fasting glucose are associated with late‐onset Alzheimer disease: Biomarkers (non‐neuroimaging): Alzheimer's disease incidence, risk factors and biomarkers. (7th December 2020) - Zhang, Xiaoling; Tong, Tong; Chang, Andrew; Ang, Ting Fang Alvin; Tao, Qiushan; Auerbach, Sandford H; Devine, Sherral; Qiu, Wendy; Mez, Jesse; Massaro, Joseph; Lunetta, Kathryn L; Au, Rhoda; et al.
Abstract: Background: Measures of cardiovascular and metabolic disease are well‐established risk factors for late‐onset Alzheimer disease (AD). However, it is poorly understood whether exposure to these risk factors in early adulthood is associated with AD incidence in late‐life. Method: Association of incident AD occurring after age 60 with measures of lipid fractions, hypertension, diabetes, blood glucose, BMI and smoking obtained prospectively across multiple exams starting in early adulthood was evaluated in the Framingham Heart Study (FHS) Offspring cohort (n = 5, 100) using Cox proportional hazard models. Three models were tested for each risk factor measured at each exam with progressive adjustment for the following covariates: Model 1 ‐ age and sex; Model 2 – age, sex, and risk factor‐specific treatment; and Model 3 – age, sex, and other vascular risk factors. Hazard ratio (HR) was calculated for a 10 mg/dL unit increase of risk factor. Result: During a mean follow‐up period of 31.7 ± 6.7 years, a consensus diagnosis of incident AD was established for 261 participants. Higher high‐density lipoprotein (HDL) measured at early (mean age =36) and midlife (mean age = 59) were associated with a decreased risk of AD (HR=0.90 [95%CI 0.83, 0.98], p=0.020 and HR=0.90 [0.79, 0.98], p=0.020, respectively). These associations remained significant after adjusting for lipid treatment. Higher triglyceride (TG) measured at these exams were associated with an increased risk of AD (HR=1.015 [1.003, 1.03], p=0.0013 and HR=1.02 [1.004, 1.04], p=0.0035, respectively). Of note, higher fasting blood glucose (FBG) measured at early, midlife and late life were associated with an increased risk of AD (HR=1.06 [1.01, 1.11], p=0.03; HR=1.08 [1.03, 1.13], p=0.0006; and HR=1.24 [1.02, 1.52], p=0.03, respectively), with attenuated associations after adjusting for diabetes treatment. In the model adjusting for other vascular risk factors, FBG at early, middle and late life remained significant. Conclusion: HDL, TG and Blood Glucose levels measured at approximately age 36 years are significantly associated with incident AD several decades later. To our knowledge this is the first evidence of the association of AD with decreased HDL level and increased TG and fasting glucose levels measured in cognitively normal individuals during early to middle adulthood.